Pengembangan Lanjut Enablink untuk Penjadwalan Pendampingan Ujian Mahasiswa dengan Disabilitas di PSLD Universitas Brawijaya - Aditya Kahfi Wicaksono; Ismiarta Aknuranda; Alies Poetri Lintangsari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
PSLD UB has Enablink service application which supports students with disabilities to get assistance during lecture activities at Brawijaya University. Currently, Enablink application has not separated lecture support schedule to exam support schedule, it leaves difficulties for the administrator to arrange the scheduling of both academic and exam supports. Some ineffective features, such as unclear licensing flows, mentoring scheduling only based on an empty companion schedule, searching for replacement supporter is done manually, and there is no notification feature so that information is often obtained through Whatsapp group. Therefore, this study aims to carry out further development of the Enablink application which can provide an exam support scheduling system and improve existing features. The system development is carried out using the rapid application development method with two iterations. The result of this research is a scheduling system for exam assistance. This study tested using a black box testing approach with validation testing and usability testing. The results of the validation test from 33 test scenarios show that the system runs as expected and functionally with 100% valid results, while the usability test gets a usability value of 78.33 (adjective rating good) using a usability scale system.